KARDIOCHIRURGIA DOROSŁYCHIntraoperative flow dynamic evaluation for single pedicled and composite arterial grafts in “off pump” coronary revascularization - Żelazny, Piotr; Szapiel, Grzegorz; Witt-Majchrzak, Anna; Buzun, Leszek; Dmyterko, Andrzej; Kukliński, Maciej; Morozow, Lew; Biederman, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction : Currently, “off pump” arterial revascularization with T and Y grafts appears to be successful surgical treatment of coronary artery disease. Aim of the study Our objective was to compare adaptive capacities of arterial grafts with one source of inflow from a single internal thoracic artery. Material and methods : Between October 2008 and July 2010, 200 patients underwent arterial revascularization without cardiopulmonary bypass. Four types of grafts were performed: single pedicled left internal thoracic artery – left anterior descending artery; single pedicled right internal thoracic artery – right coronary artery; Y grafts – two distal anastomoses; and T grafts – three or more distal anastomoses. The flow examinations were carried out with the transit-time method using VeriQ Medi Stim AS™ (Oslo, Norway). The registration of flow parameters was performed in basic conditions, and after dobutamine administration. Results : Comparing mean values of the baseline flow no differences were identified between Y and T and between single pedicled grafts (p > 0.05). Dobutamine administration resulted in significantly increased mean flows for all configurations (p < 0.005). Linear regression analysis of flow with dobutamine administration as related to baseline flow showed that the smallest increases in flow values were present in the first configuration, followed by the second and then Y and T grafts. Coronary flow reserve ranged between 1.4 and 2.01. Conclusions : Flow measurements at the basic level did not fully characterize the capability of blood flow in the arterial grafts. The examined conduits had large adaptive capacities. Flow depended upon the baseline flow value and the number of distal anastomoses.